2007
DOI: 10.1097/mlr.0b013e31806728d8
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Work Environment, Teamwork Characteristics, Burnout, and Personal Factors Upon Intent to Leave Among European Nurses

Abstract: To prevent premature leaving, it is important to expand nurses' expertise, to improve working processes through collaboration and multidisciplinary teamwork, and to develop team training approaches and ward design facilitating teamwork.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
189
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(205 citation statements)
references
References 31 publications
11
189
1
4
Order By: Relevance
“…Underappreciation has been consistently reported in studies of working conditions and is one of the main reasons associated to the shortage of nursing providers in many developed countries 7 and growing withdrawal from the nursing profession in Brazil. 3 This study corroborates fi ndings in other populations, 18 showing that the two models (demand-control and effort-reward) are complementary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Underappreciation has been consistently reported in studies of working conditions and is one of the main reasons associated to the shortage of nursing providers in many developed countries 7 and growing withdrawal from the nursing profession in Brazil. 3 This study corroborates fi ndings in other populations, 18 showing that the two models (demand-control and effort-reward) are complementary.…”
Section: Discussionmentioning
confidence: 99%
“…8 Because of this workload some providers end up withdrawing from work due to health problems 19 and giving up this occupation prematurely. 7 there are many studies on nursing, they do not assess the relationship between nurses' perceptions of their working conditions and health-related quality of life (HRQL). 3,4,14,16 HRQL is a concept and/or a form of assessment of health condition that has gained relevance in patient populations in recent decades.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Other personal factors, such as having dependents in the household, were shown to be negatively associated with organizational and professional turnover. [4,21,22] The relationship between nurses' level of education and organizational and professional turnover is less clear. Certain studies reported a positive relationship, with more educated nurses being more likely to leave an organization, whereas other studies suggested that nurses with higher educational levels (e.g.…”
Section: Individual Factorsmentioning
confidence: 99%
“…A study of hospital-based nurses from ten European countries reported that nurses' perceptions about career development opportunities were associated with increased intent to leave both organization or profession. [21] Pay and other benefits have been shown to influence nurses' intent to leave an organization and is more important for males than females. [23] However, Frijters et al reported that an increase in nurses' pay had a low impact on retention rates, which suggests that an increase in pay alone will not solve the organizational turnover issue.…”
Section: Social Work Environmentmentioning
confidence: 99%
“…In a large European survey involving more than 28,000 nurses, a high burnout score was associated with nurses' intent to leave their work setting [7]. The regular surveillance of these symptoms may prove valuable to facilitate the identification of nursing staff and ICU physicians who might benefit from additional support and to directly ascertain from interprofessional workers those potentially modifiable organizational factors they perceive to aggravate their symptoms.…”
mentioning
confidence: 99%